2018
DOI: 10.1111/ijac.12877
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of graphitic carbon spheres and their application in Al2O3‐SiC‐C refractory castables

Abstract: Graphitic carbon spheres (GCS) with an average diameter of about 0.8 μm were prepared via hydrothermal carbonization combined with catalytic graphitization using glucose and in situ formed Fe nanoparticles (NPs) as, respectively, a carbon precursor and catalyst. They were characterized by X‐ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Raman spectroscopy, and thermogravimetric analysis/differential scanning calorimetry (TG/DSC). The optimal content of Fe cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The HGCS showed sharply increased specific surface area (from 12 to 564 m 2 /g), which could be explained as follows. (1) After catalytic graphitization, the average size of the HGCS was decreased (from 0.48 to 0.35 μm) ( Figure 7 and Figure S1 ), and correspondingly about 50% weight was lost with respect to the presynthesized carbon spheres, indicating that a significant number of original oxygen containing groups were lost during the graphitization process, creating lots of new pores in the HGCS [ 20 , 28 ]; (2) the Fe(NO 3 ) 3 9H 2 O precursor not only acted as a catalyst, but also as an oxidizing agent during the graphitization process. It reacted with carbon spheres, releasing some gaseous phases such as NO x , CO, and CO 2 , which was beneficial to the physical activation of micro/meso pores formation [ 10 ]; and (3) comparison of Figure S4 and Figure 9 a revealed that, after catalyzed graphitization, the disordered carbon atoms in the original presynthesized amorphous carbon spheres were rearranged into regular graphite layers, which believed to have left some tiny gaps between the amorphous carbon layer and the regular graphite layer, and thus increased the specific surface area of the HGCS.…”
Section: Resultsmentioning
confidence: 99%
“…The HGCS showed sharply increased specific surface area (from 12 to 564 m 2 /g), which could be explained as follows. (1) After catalytic graphitization, the average size of the HGCS was decreased (from 0.48 to 0.35 μm) ( Figure 7 and Figure S1 ), and correspondingly about 50% weight was lost with respect to the presynthesized carbon spheres, indicating that a significant number of original oxygen containing groups were lost during the graphitization process, creating lots of new pores in the HGCS [ 20 , 28 ]; (2) the Fe(NO 3 ) 3 9H 2 O precursor not only acted as a catalyst, but also as an oxidizing agent during the graphitization process. It reacted with carbon spheres, releasing some gaseous phases such as NO x , CO, and CO 2 , which was beneficial to the physical activation of micro/meso pores formation [ 10 ]; and (3) comparison of Figure S4 and Figure 9 a revealed that, after catalyzed graphitization, the disordered carbon atoms in the original presynthesized amorphous carbon spheres were rearranged into regular graphite layers, which believed to have left some tiny gaps between the amorphous carbon layer and the regular graphite layer, and thus increased the specific surface area of the HGCS.…”
Section: Resultsmentioning
confidence: 99%
“…7 and Fig. S1)), and correspondingly about 50% weight was lost with respect to the pre-synthesized carbon spheres, indicating that lots of the original oxygen containing groups were lost during the graphitization process, creating lots of new pores in the HGCS [20,22]; 2) the Fe(NO3)3• 9H2O…”
Section: Microstructural Characterization Of As-prepared Hgcsmentioning
confidence: 99%
“…Presently, several technologies, including micropellets [6,7], coatings [8][9][10][11][12][13][14], and graphitic carbon spheres [15,16], have been employed to overcome the above issues. However, in practical applications, these technologies suffer from such drawbacks as discontinuous coating, aggregation and uneven distribution of carbon materials in the castables.…”
Section: Introductionmentioning
confidence: 99%